Implementation of Murabahah Agreements on Financing Products at BMT Rukun Abadi - Een Mahendra; Ulil Albab; Mawardi Mawardi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to understand the mechanism of murabahah contracts at BMT Rukun Abadi Bandar Jaya and to examine the implementation of murabahah contracts in their financing products. This study employs qualitative research with a phenomenological approach, which is adapted to observe the realities in the field through observation. Phenomenological analysis is used to analyze a phenomenon based on existing responses. Phenomenological research is used to analyze the implementation of murabahah contracts in financing products at BMT Rukun Abadi Bandar Jaya. The results of this study indicate that: 1) The mechanism of murabahah contracts at BMT Rukun Abadi Bandar Jaya consists of financing procedures, agreement terms, collateral, down payments, and penalties. 2) Implementing murabahah contracts in financing products at BMT Rukun Abadi Bandar Jaya has been well-executed, as it fulfills the criteria set within the murabahah financing mechanism. These criteria include financing procedures, agreement terms, collateral, down payments, and penalties